Emerging U.S. National Trends in the Treatment of Pediatric Supracondylar Humeral Fractures. (19th April 2017) - Holt, Joshua B.; Glass, Natalie A.; Bedard, Nicholas A.; Weinstein, Stuart L.; Shah, Apurva S.
Abstract : Background: Understanding national trends in the treatment of pediatric supracondylar humeral fractures will provide important insight into variations in regional treatment and identify areas for improving value and quality in care delivery in the U.S. Methods: U.S. national trends in the treatment of supracondylar humeral fractures were evaluated through query of the Humana (2007 to 2014) and ING (2007 to 2011) administrative claims databases. Geographic variation and changes in surgical and transfer rates over time were further explored through the Nationwide Emergency Department Sample (NEDS) database (2006 to 2011). Hospital characteristics impacting treatment decisions were identified. Results: A total of 29, 642 pediatric patients with supracondylar humeral fractures were identified in the administrative claims databases and a projected 63, 348 encounters for supracondylar humeral fracture were identified in the NEDS database. The majority of the patients (76.1%; 22, 563 of 29, 642) were treated definitively with cast immobilization. Operative treatment was performed in 23.9% of the patients (7, 079 of 29, 642), with no change observed in the operative rate over time (p = 0.055). Of patients undergoing operative treatment, closed reduction and percutaneous pinning (CRPP) was performed in 87.3%, with a significant increase noted in the rate of CRPP over time (p = 0.0001); open reduction was performed in 12.7%, with a significant decrease noted in the rate of open reduction over time (p < 0.0001). Regional surgical rates generally showed significant variation from 2006 to 2010, followed by a convergence in the surgical rate among all geographic regions in 2011. These trends occurred simultaneous to a significant increase in transfer rates nationwide, from 5.6% in 2006 to 9.1% in 2011 (p = 0.0011). Transfer rates were significantly higher (p < 0.0001) for nontrauma, nonteaching, and nonmetropolitan centers while surgical rates were significantly higher (p < 0.0001) for trauma, teaching, and metropolitan centers when rates were analyzed by hospital designation. Conclusions: Operative treatment was performed in 24% of pediatric patients with supracondylar humeral fractures from 2007 to 2014. There was a convergence of surgical rates across geographic regions, suggesting that a "standard of care" in the treatment of supracondylar humeral fractures is being established nationally. Clinical Relevance: Cases of pediatric supracondylar humeral fracture are increasingly being transferred to and, when managed surgically, receiving care at metropolitan facilities designated as trauma centers or teaching hospitals, with a corresponding decrease observed in the rate of open reduction. The optimization of nationwide referral and treatment patterns may improve value in care delivery.